Improving Data Management at Recycle Center by using Waste Management System - Koh Xin Yin; Hanayanti Hafit (Applied Information Technology And Computer Science, 2021)
Beyn NewMan Waste Solution recycle center is managing varieties of recyclable materials such as paper, plastic, aluminum, bottle, iron and so on. Currently, the target recycle center uses the waste management system for storing and managing waste material information and sales order. However, the current system consists of several issues that need to be optimized in terms of waste material management, lack of sales report function and low efficiency. The proposed system contains seven modules which are the login module, manage user module, waste attribute module, waste category module, waste material module, sales order module and sales report module. This system is developed by using the waterfall model methodology. The proposed system is written by using PHP programming language and the developed platform is Microsoft Expression Web 4. XAMPP is being used as a database server. The expected outcome of the proposed system is waste material information become well-organized, enhance the system’s efficiency by adding the manage user function and having the sales report function.